Effects of nano-selenium on cecum microbial community and metabolomics in chickens challenged with Ochratoxin A - Fang, Manxin; Hu, Wei; Liu, Ben (Frontiers in Veterinary Science, 2023)
Introduction Ochratoxin A (OTA) is a widely distributed mycotoxin. Nano-selenium (Nano-Se) is an emerging form of selenium known for its superior bioavailability, remarkable catalytic efficiency, and robust adsorbing capacity. Despite these characteristics, its impact on the microbial community and metabolomics in the cecum of chickens exposed to OTA has been infrequently investigated. This research examined the microbiota and metabolomic alterations linked to OTA in chickens, with or without Nano-Se present. Methods A cohort of 80 healthy chickens at the age of 1 day was randomly distributed into four groups of equal numbers, namely the Se cohort (1 mg/kg Nano-Se), the OTA cohort (50 μg/kg OTA), the OTA-Se cohort (50 μg/kg OTA + 1 mg/kg Nano-Se), and the control group. Each chicken group’s caecal microbiome and metabolome were characterized using 16S rRNA sequencing and Liquid chromatography coupled with mass spectrometry (LC–MS) analyses. Results and discussion Our results showed that the on day 21, the final body weight was significantly reduced in response to OTA treatments (p < 0.05), the average daily gain in the OTA group was found to be inferior to the other groups (p < 0.01). In addition, Nano-Se supplementation could reduce the jejunum and liver pathological injuries caused by OTA exposure. The 16S rRNA sequencing suggest that Nano-Se supplementation in OTA-exposed chickens mitigated gut microbiota imbalances by promoting beneficial microbiota and suppressing detrimental bacteria. Moreover, untargeted metabolomics revealed a significant difference in caecal metabolites by Nano-Se pretreatment. Collectively, the dataset outcomes highlighted that Nano-Se augmentation regulates intestinal microbiota and associated metabolite profiles, thus influencing critical metabolic pathways, and points to a possible food-additive product.